Immune dysregulation and macrophage polarization in peri-implantitis - Li, Yue; Li, Xue; Guo, Danni; Meng, Lingwei; Feng, Xianghui; Zhang, Yi; Pan, Shaoxia (Frontiers in Bioengineering and Biotechnology, 2024)
The term "peri-implantitis" (PI) refers to an inflammatory lesion of the mucosa surrounding an endosseous implant and a progressive loss of the peri-implant bone that supports the implant. Recently, it has been suggested that the increased sensitivity of implants to infection and the quick elimination of supporting tissue after infection may be caused by a dysregulated peri-implant mucosal immune response. Macrophages are polarized in response to environmental signals and play multiple roles in peri-implantitis. In peri-implantitis lesion samples, recent investigations have discovered a considerable increase in M1 type macrophages, with M1 type macrophages contributing to the pro-inflammatory response brought on by bacteria, whereas M2 type macrophages contribute to inflammation remission and tissue repair. In an effort to better understand the pathogenesis of periimplantitis and suggest potential immunomodulatory treatments for peri-implantitis in the direction of macrophage polarization patterns, this review summarizes the research findings related to macrophage polarization in peri-implantitis and compares them with periodontitis.